Stereoscopic principle in space observatory - Chubey, M.S.; Grigoriev, V.M.; Eroshkin, G.I.; L'vov, V.N.; Papushev, P.G.; Yagudin, L.I. (Кинематика и физика небесных тел, 2005)
The scientific team (ST) of the Interplanetary Solar Stereoscopic Observatory (ISSO) has got the financial support to finalize the scientific determination study with the aim to investigate the full potential of the stereoscopic idea and technical possibilities to realize the space stereoscope. The stereoscopic principle will work with optimal effectiveness in space under conditions of the stable stereoscopic base during the whole time interval of the experiment. The main conclusion of the ST up to now is that the ISSO may be created as the observatory with the flexible program, being able to support the extended solar physics investigations and the star investigations for stellar astronomy and astrophysics, being especially effective in the 3D astrometric monitoring of the motion of Solar System bodies, including near-Earth asteroids.